La Jamaïque: Système D'Information D'Agrobusiness (ABIS) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
La Rural Agricultural Development Authority (RADA) a créé l’ABIS (Agri-Business Information System) afin de fournir des informations actuelles et fiables aux petits agriculteurs.